Okun's Coefficient: A Comment - Attfield, Clifford L. F.; Silverstone, Brian (The Review of Economics and Statistics, 1997)
This paper reassesses a finding by Martin Prachowny (1993) that the value of the Okun coefficient for the United States (linking unemployment changes to output changes) is only around −0.67 rather than around the more typical value of −2.25. Using a cointegration framework, and the same data sets as Prachowny, we find, for one of the data sets, that the Okun coefficient is much closer to a value of −2.25, which supports previous research work.